2007
DOI: 10.1002/aoc.1240
|View full text |Cite
|
Sign up to set email alerts
|

Hydrosilylation of unsaturated fatty acid N‐phenyl amides

Abstract: The synthesis and the characterization of new silylated fatty acid N-phenyl amides as novel precursors for structured materials are described. Hydrosilylation of vinylic groups in terminal N-phenyl unsaturated fatty amides was efficiently catalyzed by Karstedt's catalyst. Radical initiators have been found to be active for both terminal and internal double bonds of unsaturated fatty N-phenyl amides at the necessary condition to suppress initially the conjugation in the amide function, the anilide moiety acting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Indeed, Behr et al [67,68] showed that the reactivity of internal double bonds of unsaturated fatty acid ester such as methyl linoleate is lower than that of terminal double bond. Such a low reactivity of internal double bonds was also reported in the case of fatty amide [69] and triacylglycerol [70] derivatives. The proposed reaction scheme supports the assumption that there is a conjugation of the two internal double bonds before hydrosilylation and migration of the remaining double bond in the product after reaction [67,68].…”
Section: Phospholipid Functionalized Pl-pmhs Filmssupporting
confidence: 66%
See 1 more Smart Citation
“…Indeed, Behr et al [67,68] showed that the reactivity of internal double bonds of unsaturated fatty acid ester such as methyl linoleate is lower than that of terminal double bond. Such a low reactivity of internal double bonds was also reported in the case of fatty amide [69] and triacylglycerol [70] derivatives. The proposed reaction scheme supports the assumption that there is a conjugation of the two internal double bonds before hydrosilylation and migration of the remaining double bond in the product after reaction [67,68].…”
Section: Phospholipid Functionalized Pl-pmhs Filmssupporting
confidence: 66%
“…The surfaces were prepared by grafting a natural phospholipid precursor bearing unsaturated fatty chains to PMHS films on glass or silicon. Additionally, very few studies have reported the hydrosilylation of unsaturated fatty acid derivatives [27,[63][64][65][66][67][68][69][70]. The catalytic hydrosylilation process to PMHS films gave surfaces of high densities of phospholipid 6 that are highly hydrophilic and strongly resistant to several proteins [61,62] (fibrinogen adsorption < 5 ng/cm 2 ) in comparison with other zwitterionic materials (sulfobetaine, carboxybetaine) [71,72].…”
Section: Introductionmentioning
confidence: 99%
“…Such low reactivity of an internal unsaturated fatty acid was previously reported, especially in the case of hydrosilylation of ethyl oleate: no product was obtained with H 2 PtCl 6 , and a catalytic amount of SnCl 4 as Lewis catalyst yielded only traces of the hydrochlorination product (Behr et al, 2002b). By contrast, initiation by radicals is more efficient and leads to regiospecific hydrosilylation reactions for oleic ester and oleic anilide in 90% yield (Delpech et al, 2001;El Kadib et al, 2007). As our aim in this work is to find the ideal conditions to perform the direct hydrosilylation of triacylglycerol, we first investigated the hydrosilylation of methyl linoleate which is a polyunsaturated fatty acid and is present in non-negligible quantities in fish oils (Eq.…”
Section: Hydrosilylation Of Triacylglycerolmentioning
confidence: 70%
“…Indeed, hydrometalation of fatty acid methyl esters and anilides were efficiently catalyzed by Speir's (H 2 PtCl 6 ), Wilkinson's (RhCl(PPh 3 ) 3 ) and Karstedt's (Pt 0 ) catalysts in the case of vinylic fatty acids (undecenoic methyl ester, Delpech et al, 2001) and undecenyl anilide (El Kadib et al, 2007), but less efficiently in the case of non-vinylic oils. Such low reactivity of an internal unsaturated fatty acid was previously reported, especially in the case of hydrosilylation of ethyl oleate: no product was obtained with H 2 PtCl 6 , and a catalytic amount of SnCl 4 as Lewis catalyst yielded only traces of the hydrochlorination product (Behr et al, 2002b).…”
Section: Hydrosilylation Of Triacylglycerolmentioning
confidence: 99%
“…Oils and fats are one of the most important renewable materials, since they offer a large number of possibilities for application which can be rarely met by petrochemistry. Although the hydrosilylation of olefins has been widely studied, a few reports have appeared on the fatty acid esters [69][70][71][72]. One of the examples is, the hydrosilylation of 10-undecenoyl triglyceride with multihydridosilyl moieties, such as 1,4-bis(dimethylsilyl)benzene, tetrakis(dimethylsiloxy)silane and tetramethylcyclotetrasiloxane, in the presence of Karstedt's catalyst [73] The materials obtained showed good transparency and promising properties for optical applications.…”
Section: Scheme 81 Carboranylene Siloxanes (1 and 2) And Siloxane Crmentioning
confidence: 99%